MENUJU TATA KELOLA PENDIDIKAN CERDAS: TINJAUAN LITERATUR SISTEMATIS TENTANG INTEGRASI APLIKASI PERUSAHAAN, SISTEM PEMBELAJARAN DIGITAL, MANAJEMEN PENGETAHUAN, DAN INTELIJEN BISNIS - Firda Prasetyowati; Deasy Rolla Jayanti; Sugeng Listyo Prabowo (Pascasarjana Universitas Pendidikan Ganesha, 2026)
Digital transformation demands more efficient, transparent, and accountable education governance. However, studies on the four main pillars of Management Information Systems (MIS): enterprise applications, digital learning systems, knowledge management, and business intelligence, are generally conducted separately, resulting in the lack of a conceptual framework that integrates them. This study aims to formulate an integrative conceptual framework that explains the interrelationships of these four pillars in supporting education governance in the digital era. The study employed a qualitative approach with the PRISMA-based Systematic Literature Review (SLR) method. Literature searches were conducted through Google Scholar using Harzing's Publish or Perish applications with predetermined inclusion criteria, resulting in six articles meeting the requirements for thematic analysis. The synthesis results indicate that enterprise applications provide an integrated data foundation, digital learning systems support technology-based learning processes, knowledge management maintains the sustainability of institutional knowledge, and business intelligence transforms data into a basis for strategic decision-making. These four pillars form a complementary information value chain, with successful implementation determined by the alignment of institutional strategy, human resource digital competence, and leadership commitment. The resulting conceptual framework is expected to serve as a reference for the development of empirical research and the formulation of digital education governance policies.